The Application of Ai-Based Audio-Visual Learning Media To Student Learning Interest In The Subject of Islamic Cultural History In Madrasah Ibtidaiyah - Abu Mansur; Zuhdiyah Zuhdiyah; Nurlaeli Nurlaeli (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
In the digital era the learning process is directed to computerization such as the application of Competency-Based National Assessment (ANBK) all schools have implemented computerization as well as MI Azizan Palembang has started the learning process and assessment using computer media, the purpose of this study was carried out to determine the Application of Interactive Video Learning Media at Madrasah Ibtidaiyah Azizan, the Effect of Application of Interactive Video on Student Learning Interest, the research method in this study used an experimental method with a pre-test post test design, data collection techniques in this study using questionnaires, interviews and documentation, data analysis techniques carried out with simple linear regression. The research uses validity, reliability, and hypothesis testing, the results of the study, the learning process at MI Azizan has been running properly, from the results of the calculation of the simple regression test shows the significance value of 0.000 <0.05. so it can be concluded that the media used has a significant effect in developing students' learning interest. meaning that Ha which reads